“Conscious, committed and responsible”: Professional futures, higher education and social values - McCarthy, Michael C. (Razón y fe, 2019)
This article raises the desirability and necessity of values in the field of higher education. In order to accomplish this mission, universities should not only be understood as organizations, but also as institutions that infuse into their environments values that go beyond the technical requirements of the task at hand. This vision is in line with the Jesuit educational tradition, which has been updated by identifying four final objectives: utility, justice, humanity and faith.